Revisiting the impact of genomic hot spots: C12orf35 locus as a hot spot and engineering target - Cho, Kyuhee; Lee, Jae Seong (Biotechnology and Bioengineering, 2024)
Traditional Chinese hamster ovary (CHO) cell line development is based on random integration (RI) of transgene that causes clonal variation and subsequent large-scale clone screening. Therefore, site-specific integration (SSI) of transgenes into genomic hot spots has recently emerged as an alternative method for cell line development. However, the specific mechanisms underlying hot spot site formation remain unclear. In this study, we aimed to generate landing pad (LP) cell lines via the RI of transgenes encoding fluorescent reporter proteins flanked by recombination sites to facilitate recombinase-mediated cassette exchange. The RI-based LP cell line expressing high reporter levels with spontaneous C12orf35 locus deletion exhibited similar reporter fluorescent protein levels compared to targeted integrants with an identical reporter LP construct at the CHO genome hot spot, the C12orf35 locus. Additionally, Resf1, a C12orf35 locus gene, knockout (KO) in the RI-based LP cell line with conserved C12orf35 increased reporter expression levels, comparable to those in cell lines with C12orf35 locus disruption. These results indicate that the effect of SSI into the C12orf35 locus, a genomic hot spot, on high-level transgene expression was caused by C12orf35 disruption. In contrast to C12orf35 KO, KO at other well-known hot spot sites at specific loci of genes, including Fer1L4, Hprt1, Adgrl4, Clcc1, Dop1b, and Ddc, did not increase transgene expression. Overall, our findings suggest that C12orf35 is a promising engineering target and a hot spot for SSI-based cell line development.
Keywords: C12orf35; Cell lines; Chinese hamster ovary; CRISPR/cas9; Genomics; Hotspots; Landing pads; Site-specific; Transgene; Animals; CHO Cells; Cricetulus; Transgenes; C12orf35; Chinese hamster ovary (CHO); CRISPR/Cas9; hot spot